Mind your cart - Chan, Desiree Wan Rong (Nanyang Technological University, 2021)
Mind Your Cart (MYC) is a communications campaign aimed at encouraging young Singaporeans aged 18 to 25 to practice conscious consumption of fashion to better their everyday well-being. It reframed fashion consumption beyond environmental sustainability, highlighting that overspending time, effort, and money on fashion can have a dampened effect on one’s well-being. Framed by the Self-Determination Theory that posits the three basic psychological needs of autonomy, competence, and relatedness, conscious consumption appeals to the inherent human propensity for growth and development. The campaign promoted two main behaviours that constitute conscious consumption: using a checklist during pre-purchase and creating a wardrobe inventory. The digital campaign framed conscious consumption as a dynamic journey guided by the tagline "Check In Before You Check Out". Through strategic campaign tactics built on the pillars of 'Educate, 'Engage' and 'Encourage', MYC was successful in cultivating a belief framework about conscious consumption and equipping our target audience with practical skills on how to use a checklist and create an inventory. The campaign received significant digital traction with a total of 106,111 impressions, a 10.07% engagement rate on Instagram, and an average of 33% in behaviour uptake.